2018
DOI: 10.1177/1750481318817621
|View full text |Cite
|
Sign up to set email alerts
|

The pragmatic-semiotic construction of male identities in contemporary advertising of male grooming products

Abstract: This article aims to unveil how male identities are constructed in a corpus of male toiletry TV ads through a pragmatic and multimodal analysis of a set of implicit assumptions conveyed about the male participants in the ads. The validity of these assumptions is first empirically tested with a group of 10 male informants and then those implied meanings are bundled into thematic cores for their qualitative and quantitative description. Findings reveal that these ads still rely on stereotypical constructs and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Pola informasi yang disajikan perusahaan adalah pola deduksi dari fakta, data, dan minat konsumen tentang sesuatu produk, sedangkan konsumen menginginkan informasi yang rinci dan jujur tentang produk itu. Selain itu, perusahaan juga tidak jarang mereduksi informasi, bahkan informasi utama tentang kelebihan dan kekurangan produk yang diiklankan (Ain et al, 2023;Del Saz-Rubio, 2019). Di sisi lain, konsumen akan langsung memiliki interpretasi dan ekspektasi terhadap sebuah produk dari konten iklan yang dipublikasikan yang terkadang tidak sesuai dengan kenyataan.…”
Section: A Pendahuluanunclassified
See 1 more Smart Citation
“…Pola informasi yang disajikan perusahaan adalah pola deduksi dari fakta, data, dan minat konsumen tentang sesuatu produk, sedangkan konsumen menginginkan informasi yang rinci dan jujur tentang produk itu. Selain itu, perusahaan juga tidak jarang mereduksi informasi, bahkan informasi utama tentang kelebihan dan kekurangan produk yang diiklankan (Ain et al, 2023;Del Saz-Rubio, 2019). Di sisi lain, konsumen akan langsung memiliki interpretasi dan ekspektasi terhadap sebuah produk dari konten iklan yang dipublikasikan yang terkadang tidak sesuai dengan kenyataan.…”
Section: A Pendahuluanunclassified
“…Aspek sosiopragmatik menitikberatkan pada bagaimana bahasa digunakan dalam masyarakat. Kesadaran konsumen terhadap ketulusan tertentu memiliki pengaruh yang signifikan terhadap aset merek seperti pengakuan terhadap merek, niat beli, dan loyalitas terhadap merek (Bolognesi & Lievers, 2020;Del Saz-Rubio, 2019). Di sisi lain, dalam bidang psikologi, ketulusan diartikan sebagai nilai, keyakinan, pikiran, dan perasaan individu sesuai dengan diri yang sebenarnya dan jujur pada dirinya sendiri.…”
Section: A Pendahuluanunclassified
“…Ronny also establishes clear body aspirations via his engagement with UFC 1 stating ‘oh my god imagine if I could look like that’. This demonstrated that media images play a role in how the men articulate their emotions related to body envy and how they establish aspirations for their own bodies (Saz and Rubio, 2019). That is, men are exposed to hegemonic archetypes of male bodies that are used to evaluate their own bodies.…”
Section: Wayne’s Mood Boardmentioning
confidence: 99%
“…There have been several studies that examine advertising using a semiotic approach, among other are Firdaus (2018), Yücel (2019), Ardhianto and Son (2019), Wong (2019), andDel Saz-Rubio (2019). Focusing on French advertisements, Syahdini (2019) studied the connotation in a video advertisement by L'Oreal Paris; while Fatma (2021) analyzed various images in telephone operators' advertisements in Tunisia, and Yasmine (2021) focused on the existence of hidden meanings in the advertisements of the most widely used products during the Covid-19 pandemic in France.…”
Section: Introductionmentioning
confidence: 99%